5(n-7)-(6-4n)=8n

Simple and best practice solution for 5(n-7)-(6-4n)=8n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(n-7)-(6-4n)=8n equation:


Simplifying
5(n + -7) + -1(6 + -4n) = 8n

Reorder the terms:
5(-7 + n) + -1(6 + -4n) = 8n
(-7 * 5 + n * 5) + -1(6 + -4n) = 8n
(-35 + 5n) + -1(6 + -4n) = 8n
-35 + 5n + (6 * -1 + -4n * -1) = 8n
-35 + 5n + (-6 + 4n) = 8n

Reorder the terms:
-35 + -6 + 5n + 4n = 8n

Combine like terms: -35 + -6 = -41
-41 + 5n + 4n = 8n

Combine like terms: 5n + 4n = 9n
-41 + 9n = 8n

Solving
-41 + 9n = 8n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-8n' to each side of the equation.
-41 + 9n + -8n = 8n + -8n

Combine like terms: 9n + -8n = 1n
-41 + 1n = 8n + -8n

Combine like terms: 8n + -8n = 0
-41 + 1n = 0

Add '41' to each side of the equation.
-41 + 41 + 1n = 0 + 41

Combine like terms: -41 + 41 = 0
0 + 1n = 0 + 41
1n = 0 + 41

Combine like terms: 0 + 41 = 41
1n = 41

Divide each side by '1'.
n = 41

Simplifying
n = 41

See similar equations:

| 2t+5=9-t | | s+(3s+0.22)+(s-0.22)=4.6 | | (4+256)+(445*86)= | | x-0.08=0.1 | | -5x-8(x+5)=-4(3x+8) | | 3(2+b)-4b=b+16 | | -8(m+8)=-9+3m | | (4+256)+(47*86)= | | 17+y=20 | | x+2=93 | | 4x-60=2x+10 | | 5y-8y=-18 | | (4+256)+(47*86)-34= | | -7.9+x=-33.7 | | .75+1.5x=0.46+0.4x+0.5 | | 11.3=4.5+w | | 2w+36=-4w | | tx-q=z | | 4(x-2)=5(x-1)+3x+1 | | -25.6=-2.6+m | | 2400+4.00x=2100 | | 3(n+5)-6=3(n+3) | | 7x+4x=(7+4)x | | -7(v+4)+4v+7=5v+9 | | -2[h-7]=-28 | | x+45=-29 | | h+7.74=7.2 | | 5x-9(x+1)+(5x-1-2)=9 | | -5/8-5/12= | | -6(n-2)=9-5n | | -3(4-3z)=4z+3 | | 5x+24-x=21 |

Equations solver categories